The Impact of Funding from the Rural Development Programme for 2007-2013 on the Functioning of Chosen Agricultural Holding (Research Bulletins of the Faculty of Economic Sciences, 2015)
The aim of this article is to discuss the impact of funding from The Rural Development Programme for 2007-2013 on the functioning of chosen indyvidual agricultural holding. In the area of The Rural Development Programme for 2007-2013 the studied agricultural holding benefited from the three measures of axis 1: setting-up of youngfarmers, early retirement and modernisation of agricultural holdings. Implemented measures influenced significantly to the development and functioning of the holding.
Keywords: funding; The Rural Development Programme for 2007-2013; indyvidual agricultural holding